Association of Viral Infection With the Development and Pathogenesis of Systemic Lupus Erythematosus - Iwata, Shigeru; Tanaka, Yoshiya (Frontiers in Medicine, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease that causes multiple organ damage in women of childbearing age, and has a relapsing-remitting course. SLE is caused by the interaction between genetic and environmental factors. However, its underlying triggers remain unknown. Among the environmental factors, the involvement of infections as a trigger for SLE, especially those of viral etiology, has been widely reported. Human endogenous retroviruses (HERVs) may put patients at a genetic predisposition to SLE, while the Epstein-Barr virus (EBV) may play a role as an environmental factor that triggers the development of SLE. It has been suggested that EBV-infected B cells may become resistant to apoptosis, resulting in the activation, proliferation, and antibody production of autoreactive B cells, which cause tissue damage in SLE. However, the interaction between the virus and immune cells, as well as the impact of the virus on the differentiation and dysfunction of immune cells, remain unclear. In this review, we focus on the relationship between the development and pathogenesis of SLE and viral infections, as well as the mechanism of SLE exacerbation via activation of immune cells such as B cells, based on the latest findings.